The effect of washing on the dimensional stability and absorbency of poly-cotton white crew neck shirt - Vidanes, Olive Escarmosa
This is an experimental study about the effect of washing on the dimensional stability and absorbency of poly-cotton white crew-neck shirt. The main objective of this study is to determine the change in the dimensional stability and level of absorbency of white crew neck shirt before and after washing. Laboratory test methods provided by the Philippine Textile Research Institute were used in this study, The experiment consisted of two different processes: plain washing and washing with fabric conditioner. Three samples were subjected to each process to determine dimensional change and absorbency of Blue Corner poly-cotton white crew-neck shirt. For the purpose of this study, a random sampling method of gathering the specimens as used. The results of the laboratory tests done in PTRI were the primary sources of data. Results showed that washing had a shrinkage effect on poly-cotton white crew-neck shirt regardless of the process. However, he absorbency capacity increased with the number of washing. In addition, test results showed that the poly-cotton garment absorbs water faster when washed with fabric conditioner than with plain washing.